Leachate Treatment Using Limestone Filled-Tank and Constructed Wetland - Nadiah, Mokhtar; Noor Suraya, Romali; Siti Fatimah, Che Osmi (2012)
The suitability of eco-limestone filter, consist of limestone filter and constructed wetland (CW) to treat the landfill leachate were investigated. The systems offer an eco-engineering leachate treatment using limestone filter (abiotic component) and wetland (biotic component). A continuous flow mode study has been used to treat raw leachate from Kuantan Landfill. In this study, limestone sized of 14mm, 10mm and 5mm with the ratio of 10:20:70 were used as a filter media in limestone-filled tank. Two types of CW have been applied; sub-surface flow (SSF) system and free water surface (FWS) system. The treated leachate was analyzed for pH, BOD, COD and heavy metal such as Pb, Cu, Mn, Zn and Cr. The results demonstrate that eco-limestone filter was effective to treat leachate especially by using SSF system. The pH of leachate wastewater before and after treatment was complying with standard for discharge leachate as stated in Environmental Quality (Control of Pollution from Solid Waste Transfer Station and Landfill) Regulations 2009 published by Department of Environment (DOE). For BOD , the percentage removal was gradually increased with the increase of contact time. The removal was recorded up to 56% and 50% using SSF and FWS, respectively. The COD, Ammoniacal Nitrogen (A-N) and TSS were removed up to 97%-99% for both systems. Meanwhile, for heavy metals, both systems were capable to attenuate heavy metal and removed it from leachate up to 100%. The system has been run for 10 days contact time, with the flowrate, Q= 4L/min. 5